Іnfluence of crop pollution on development i maize productivity - Sergienko, V.; Tyshchuk, O.; Borodai, V. (Quarantine and plant protection, 2023)
Goal. To study the reserves of weed seeds in the soil and to determine the influence of weediness of crops on the development and productivity of corn. Methods. Informational and analytical (collection of materials and analysis of literary sources), field and laboratory research (setting up experiments, soil analysis, monitoring plant development, determination of biometric indicators, accounting for the number of weeds, collection and determination of crop structure), mathematical and statistical (processing of research results). The design of the field experiment included weeded and weed-protected plots. Results. In the forest-steppe zone of Ukraine, with intensive corn cultivation technology, the average number of weeds in the soil from emergence to row closure was at the level of 250—425 weeds/m2. Determining the number and species composition of segetal vegetation made it possible to establish that the corn crops are dominated by a mixed type of weediness with the dominance of annual dicotyledonous and grassy weeds. The number of dominant weeds at the beginning of the corn growing season in the experimental plots of NUBiP (Kyiv) was: Chenopodium album L. — 16 pcs./ m2, Amaranthus retroflexus L. — 23 pcs./m2, Portulaca oleracea L. — 78 pcs./ m2. In the fields of the agricultural station (Fastivskyi district), the dominant weeds were Polygonum convolvulus L., Setaria glauca L., Chenopodium album L., the number of which in the phase of 4—5 leaves was 32, 20 and 10 pcs./m2, respectively. Weeds significantly limited the growth of corn both in terms of plant height and development phases. In the phase of 9—10 leaves of corn in the weeded area, some types of weeds reached the height of the corn, accumulated a significant vegetative mass and began to form reproductive organs. The above-ground mass of weeds at the beginning of grain formation reached 995 g/m2. The pollution of the crops significantly affected the reduction of the corn yield and its structure. Conclusions. Significant reserves of weed seeds in corn crops cause the development of segetal vegetation during its growing season. The high competitiveness of weeds was manifested in the suppression of the growth and development of the culture and the formation of the crop. Weeds form a significant vegetative mass and reproductive organs at the beginning of the development of the corn grain. On weedy crops, the yield of corn decreased by an average of 32—35%.